Speaking skills strategies and its relationship with language anxiety among Arabic language students in selected universities / Muhammad Hasan - Muhammad , Hasan (2019)
Learning strategies play an important role in language learning particularly in speaking learning. The use of strategies is often associated with language anxiety. This study aimed (i) to determine speaking skills strategies used by students (i) to identify the levels of language anxiety, (iii) to identify the differences between the use of speaking skills strategies and language anxiety according to gender, university, and duration of study, (iv) to examine the relationship between speaking skills strategies and language anxiety. This survey method used two sets of questionnaires, namely the Second Language Speaking Strategies (Wahyuni, 2013) and Foreign Language Speaking Anxiety Scale (FLSAS) (Öztürk & Gürbüz, 2014) which have been modified into Arabic contexts and have tested validity and reliability which were accepted (alpha value 0.60- 0.83). 320 people as research respondents were selected using the purposive sampling method. The results showed that there were two learning strategies used by students at a high level namely metacognitive and compensation strategies, while the other four strategies were at a moderate level, namely memory, affective, cognitive, and social strategies. The study found that the level of language anxiety was at a low level with test anxiety being the lowest, followed by fear of negative evaluation, and communication apprehension. The results also showed that there were significant differences in the use of speaking skills strategies based on university, the level of language anxiety based on gender and university, whereas there was no significant difference between gender and duration of study. Three types of learning strategies namely memory, cognitive, and social strategies have a positive relationship with students’ language anxiety.